Die aanwending van persoonlike beskermende toerusting met die oog op die skep van 'n geborgenheidsruimte in Tegnologie-skoolwerkwinkels (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2023)
Section 24 of the Occupational Health and Safety Act (85 of 1993) sets requirements that must be met in school technology workshops regarding the use of personal protective equipment. These measures are aimed at ensuring the safety of the teachers and learners in such workshops. This article reports on the findings of a mixed research investigation in South African technical schools that offer Mechanical Technology as a subject. The investigation aimed at determining the nature, extent and management of accidents and injuries in the Mechanical Technology workshops of schools. It was, more specifically, aimed at discovering whether the use or non-use of personal protective equipment by injured individuals played any role in the case of accidents. The investigation revealed that the failure to wear personal protective equipment or clothing, and/or the incorrect use thereof, was indeed the cause of a large number of accidents in the workshops. Because there is a legal as well as a reformational-ethical obligation on Mechanical Technology teachers to ensure the safety of all the role players in the workshop, it is necessary for such teachers to be aware of all the requirements in relation to protective equipment, and to adhere appropriately to them  in order to ensure the safety, particularly the personal safety, of the learners in the workshop.